Mold Surface Profile Processing Characteristic and Mold Design of Double Helical Synchronous Belt - Hu Qingming; Guo Jianhua; Zhang Guangbin; Wu Yizhen (Jixie chuandong)
The double helical synchronous belt has received great concern for its high loading capacity,low transmission error and noise. Through the gear profile curve parameter analysis of synchronous belt and pulley,the gear profile equation is established by using the high order contact meshing theory. The mold gear surface profile processing characteristic is investigated and the mold surface equation of double helical synchronous belt is deduced according to the coordinate transformation and gear meshing principles. Finally,the combined detachable mold is proposed to manufacture four belts simultaneously. The proposed mold is used to guide the production practice.